Effect of pine fiber on concrete compressive and flexural strength - Muhammad Syafiq , Mansoruddin (2013)
There are having been many efforts made to increase the capacity and strength in concrete technology. The use of natural fibers in concrete technology is one of the techniques used to achieve these objectives. The use of natural fibers as an additive in concrete is not widespread and not yet found a place in the industry. This research was carried out to establish the effects of pine fiber addition on concrete compressive and flexural strength. In this study, a total of 36 cubes (150mm x 150mm x 150 mm) and 12 small beams (100mm x 100mm x 500 mm) were prepared according to three types of mixture proportion and all these samples were cured in water curing for 7 days, 14 days and 35 days. The three types of concrete mixture used in this research were concrete containing 0.1% pine fiber, 0.2% pine fiber and 0.3% pine fiber and plain concrete as control sample. The test results showed that the 0.1% pine fiber content is the optimum percentage of pine fiber additional. Even though the compressive strength result does not show the satisfied result, but the flexural strength of concrete is increased for 0.1% pine fiber. However, the strength of concrete does not increase with increasing of fiber content. The results show a good sign for further investigation to increase the flexural strength of concrete in presence of pine fiber as additive.